Factorial Design Optimization of Antioxidant Cream from Kepok Banana Peel Extract: Formulation, Characterization, and Stability Evaluation - Gabriella Sharen Allolinggi; Wahyuning Setyani (HM Publisher, 2025)
Kepok banana peel, a rich source of flavonoids and phenols with potent antioxidant activity, presents a promising natural ingredient for topical applications. This study aimed to optimize the formulation of an antioxidant cream using kepok banana peel ethanol extract, focusing on the emulsifier combination of stearic acid and triethanolamine (TEA) for enhanced physical properties and stability. A two-factor, two-level factorial design was employed to investigate the effects and interactions of stearic acid and TEA concentrations on the cream's organoleptic characteristics, homogeneity, pH, viscosity, and spreadability. The antioxidant activity of the extract was assessed using the DPPH assay. The optimal formula was determined using Design Expert 13 software with ANOVA at a 95% confidence level. The ethanol extract exhibited strong antioxidant activity (IC50 84.25 ppm). The optimal cream formulation, containing 10 grams of stearic acid and 2 grams of TEA, demonstrated desirable physical properties, including smooth texture, homogenous appearance, and excellent spreadability, meeting the criteria for a stable and effective topical product. In conclusion, Kepok banana peel extract holds significant potential as a natural antioxidant for topical applications. The optimized cream formulation, achieved through factorial design, provides a stable and effective delivery system for harnessing the therapeutic benefits of this natural extract.